Dampak Perkembangan Teknologi Dikalangan Remaja Dilihat dari Nilai-Nilai Karakter - Riska Mayeni; Okviani Syafti; Sefrinal Sefrinal (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This study aims to determine and analyze the impact of technological development among adolescents as seen from the character values including the positive and negative impacts of technology mining among adolescents as seen from character values. This research uses a qualitative approach. Respondents in this study were all students of SMA Negeri 2 Linggo Sari Baganti totaling 89 people with rondom sampling technique as much as 25% of the total number of students. Data were collected using interview and observation techniques. While the data source is the principal, teachers and students of SMAN 2 Linggo Sari Baganti. The results showed that the positive impact of technological development in education is able to create good learning activities, make it easier for students to find learning resources, and with technology can help students learn to implement technology in teaching and learning, so students are more interesting to learn. The findings also show that the negative impact of technological development, one of which is the low value of character, especially from the social aspect, lack of student communication with the surrounding environment, low levels of caring among peers and technological development is also misused for games that make them forget themselves.